2020
DOI: 10.35119/asjoo.v17i1.441
|View full text |Cite
|
Sign up to set email alerts
|

Difference in prevalence of diabetes and diabetic retinopathy among low-altitude dwellers vs. high-altitude dwellers in North India

Abstract: Background: Type-2 diabetes mellitus (DM) is one of the leading lifestyle-related chronic disease as its prevalence is expected to rise up to 24.0% in the world by 2025, which was only 6.3% in year 2003. Objective: To understand the high-altitude and low-altitude differentials for DM and diabetic retinopathy (DR) prevalence in a sub-Himalayan state of North India. Methods: The study was carried out in the Shahpur block of Kangra district (altitude 2,404 feet) and the Spiti block of Lahaul and Spiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Although some studies have suggested the beneficial effects of living at HA on glucose homeostasis, the relationship between HA and DR remains unclear owing to multiple factors and potential confounders, such as varying altitudes of the investigated population, duration of exposure to HA, genetic backgrounds, living conditions, dietary habits, and physiological adaptation. Table 1 summarizes the main findings of previous studies [9][10][11][12][13][14][15] that explored the impact of HA on DR. This review aimed to comprehensively explore the impact of HA exposure on DR, encompassing genetic adaptations, changes in glucose homeostasis, and related factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have suggested the beneficial effects of living at HA on glucose homeostasis, the relationship between HA and DR remains unclear owing to multiple factors and potential confounders, such as varying altitudes of the investigated population, duration of exposure to HA, genetic backgrounds, living conditions, dietary habits, and physiological adaptation. Table 1 summarizes the main findings of previous studies [9][10][11][12][13][14][15] that explored the impact of HA on DR. This review aimed to comprehensively explore the impact of HA exposure on DR, encompassing genetic adaptations, changes in glucose homeostasis, and related factors.…”
Section: Introductionmentioning
confidence: 99%